Post occlusive left atrial appendage thrombosis with extension into the left atrium - Shalaby, Alaa (BMJ Publishing Group, 2014)
A 67-year-old man underwent left atrial appendage (LAA) exclusion concomitant with mitral valve surgery and radiofrequency ablation maze procedure. On transoesophageal echocardiography anticipating ablation for left atrial tachycardia, an echodense thrombus was visualised in the LAA location with apparent intracavitary extension into the left atrium. Based on CT imaging findings, the echo represented thrombosis of a large left atrial appendage with probable extension into the left atrium.